Maternal Immune Dysregulation and Autism–Understanding the Role of Cytokines, Chemokines and Autoantibodies - McLellan, Janna; Kim, Danielle H. J.; Bruce, Matthew; Ramirez-Celis, Alexandra; Van de Water, Judy (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) is acknowledged as a highly heterogeneous, behaviorally defined neurodevelopmental disorder with multiple etiologies. In addition to its high heritability, we have come to recognize a role for maternal immune system dysregulation as a prominent risk factor for the development of ASD in the child. Examples of these risk factors include altered cytokine/chemokine activity and the presence of autoantibodies in mothers that are reactive to proteins in the developing brain. In addition to large clinical studies, the development of pre-clinical models enables the ability to evaluate the cellular and molecular underpinnings of immune-related pathology. For example, the novel animal models of maternal autoantibody-related (MAR) ASD described herein will serve as a preclinical platform for the future testing of targeted therapeutics for one ‘type’ of ASD. Identification of the cellular targets will advance precision medicine efforts toward tailored therapeutics and prevention. This minireview highlights emerging evidence for the role of maternal immune dysregulation as a potential biomarker, as well as a pathologically relevant mechanism for the development of ASD in offspring. Further, we will discuss the current limitations of these models as well as potential avenues for future research.